0% found this document useful (0 votes)
2 views

Module 2 (Chapter 1)

This document discusses the properties of integers, focusing on the well-ordering principle and mathematical induction. It explains the steps involved in mathematical induction, providing examples to illustrate how to prove statements for all natural numbers. The document includes several proofs using induction to demonstrate various mathematical formulas.

Uploaded by

bunnyverse18
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
2 views

Module 2 (Chapter 1)

This document discusses the properties of integers, focusing on the well-ordering principle and mathematical induction. It explains the steps involved in mathematical induction, providing examples to illustrate how to prove statements for all natural numbers. The document includes several proofs using induction to demonstrate various mathematical formulas.

Uploaded by

bunnyverse18
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 18

MODULE – 2 CHAPTER 1

PROPERTIES OF INTEGERS

2.1 THE WELL ORDERING PRINCIPLE

The well-ordering principle says that the positive integers are well-ordered. An
ordered set is said to be well-ordered if each and every nonempty subset has a smallest or
least element. So the well-ordering principle is the following statement:
Every nonempty subset S of the positive integers has a least element.

2.2 MATHEMATICAL INDUCTION

Mathematical Induction is a mathematical technique which is used to prove a


statement, a formula or a theorem is true for every natural number. This technique involves
two steps to prove a statement, as stated below:
Step 1: (Basis step): It proves that a statement is true for the initial value.
Step 2: (Inductive step): It proves that if the statement is true for the nth iteration (or
number n), then it is also true for (n + 1)th iteration ( or number n + 1).
Principle of Mathematical induction
Let P(n) be the given statement or formula involving only natural numbers. Then P(n)
is true for all positive integers n if
(i) P(1) is true
(ii) P(k) is true  P(k + 1) is true
Working Procedure
Let P(n) be the given statement or formula involving only natural numbers. In order to
prove that a statement or formula P(n) is true for all positive integers n, we first verify that
the result is true for n = 1. Then we assume that the result is true for n = k. Using this we
prove that the result is true for n = k + 1.
2 Properties of Integers
--------------------------------------------------------------------------------------------------------------------------------------

Examples
n  n  1
1. Prove by Mathematical Induction 1 + 2 + 3 + ... + n =  n  N.
2
Solution:
n  n  1
Let P(n) = 1 + 2 + 3 + ... + n =  n  N.
2
Step 1: For n =1,
11  1 2
LHS = 1 and RHS =  1
2 2
So, LHS = RHS
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
k  k  1
Hence, P(k) = 1 + 2 + 3 + ... + k =  k  N.
2
To show that P(k + 1) is true
 k  1   k  1  1
i.e., P(k + 1) = 1 + 2 + 3 + ... + (k + 1) =  k  N.
2

 P(k + 1) = 1 + 2 + 3 + ... + (k + 1) =
 k  1 k  2   k  N.
2
Consider, LHS = 1 + 2 + 3 + ... + (k + 1)
= 1 + 2 + 3 + ... + k + (k + 1)
k  k  1
= + (k + 1) (by using P(k))
2
k  k  1  2  k  1
=
2

=
 k  1 k  2 
2
= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

2. Prove by Mathematical Induction 1 + 3 + 5 + ... + (2n −1) = n2 for n = 1, 2, 3…


Solution:
Let P(n) = 1 + 3 + 5 + ... + (2n −1) = n2 for all n  N.
Step 1: For n =1,
LHS = 1 and RHS = 12 = 1
Discrete Mathematical Structures 3
-------------------------------------------------------------------------------------------------------------------------------------

So, LHS = RHS


 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = 1 + 3 + 5 + ... + (2k −1) = k2 for all k  N.
To show that P(k + 1) is true
i.e., P(k + 1) = 1 + 3 + 5 + ... + (2(k + 1) −1) = (k + 1)2
 P(k + 1) = 1 + 3 + 5 + ... + (2k + 1) = (k + 1)2
Consider, LHS = 1 + 3 + 5 + ⋯ + (2k + 1)
= 1 + 3 + 5 + ⋯ + (2k −1) + (2k + 1)
= k2 + (2k + 1) (by using P(k))
= (k + 1)2
= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

n  n  1 2n  1
3. Prove by Mathematical Induction 12 + 22 + 32 + ... + n2 =  n  N.
6
Solution:
n  n  1 2n  1
Let P(n) = 12 + 22 + 32 + ... + n2 =  n  N.
6
Step 1: For n =1,
11  1 2  1 1 2  3
LHS = 12 = 1 and RHS =  1
6 6
So, LHS = RHS
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
k  k  1 2k  1
Hence, P(k) = 12 + 22 + 32 + ... + k2 =  k  N.
6
To show that P(k + 1) is true
 k  1   k  1  1  2  k  1  1
i.e., P(k + 1) = 12 + 22 + 32 + ... + (k + 1)2 =
6

 P(k + 1) = 12 + 22 + 32 + ... + (k + 1)2 =


 k  1 k  2  2k  3
6
Consider, LHS = 12 + 22 + 32 + ... + (k + 1)2
= 12 + 22 + 32 + ... + k2 + (k + 1)2
4 Properties of Integers
--------------------------------------------------------------------------------------------------------------------------------------

k  k  1 2k  1
= + (k + 1)2 (by using P(k))
6
k  k  1 2k  1  6  k  1
2

=
6
 k  1  k  2k  1  6  k  1 
=
6
 k  1  2k 2
 7 k  6 
=
6
 k  1  2k 2  4k  3k  6
=
6
 k  1  2k  k  2   3  k  2 
=
6

=
 k  1 k  2  2k  3
6
= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

n 2  n  1
2

4. Prove by Mathematical Induction 1 + 2 + 3 + ... + n = 3 3 3 3


 n  N.
4
Solution:
n 2  n  1
2
3 3
Let P(n) = 1 + 2 + 3 + ... + n = 3 3
 n  N.
4
Step 1: For n =1,
12 1  1 1 4 
2
3
LHS = 1 = 1 and RHS =  1
4 4
So, LHS = RHS
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true

k 2  k  1
2
3
Hence, P(k) = 1 + 2 + 3 + ... + k = 3 3 3
 k  N.
4
To show that P(k + 1) is true

 k  1   k  1  1
2 2

i.e., P(k + 1) = 13 + 23 + 33 + ... + (k + 1)3 =


4
 k  1  k  2 
2 2

 3 3
P(k + 1) = 1 + 2 + 3 + ... + (k + 1) = 3 3
4
3 3 3 3
Consider, LHS = 1 + 2 + 3 + ... + (k + 1)
Discrete Mathematical Structures 5
-------------------------------------------------------------------------------------------------------------------------------------

= 13 + 23 + 33 + ... + k3 + (k + 1)3

k 2  k  1
2

= + (k + 1)3 (by using P(k))


4
k 2  k  1  4  k  1
2 3

=
4
 k  1  k 2  4  k  1
2

=
4
 k  1  k 2  4k  4 
2

=
4
 k  1  k  2 
2 2

=
4
= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

5. Prove by mathematical induction for all positive integers n, that


n  n  1 2n  7 
1.3 + 2.4 + 3.5 + ... + n(n + 2) = .
6
Solution:
n  n  1 2n  7 
Let P(n) = 1.3 + 2.4 + 3.5 + ... + n(n + 2) =  n  N.
6
Step 1: For n =1,
11  1 2  7   2  9 
LHS = 1.3 = 3 and RHS =  3
6 6
So, LHS = RHS
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
k  k  1 2k  7 
Hence, P(k) = 1.3 + 2.4 + 3.5 + ... + k(k + 2) =  k  N.
6
To show that P(k + 1) is true
 k  1   k  1  1  2  k  1  7 
i.e., P(k + 1) = 1.3 + 2.4 + 3.5 + ... + (k + 1)((k + 1) + 2) =
6

 P(k + 1) = 1.3 + 2.4 + 3.5 + ... + (k + 1)(k + 3) =


 k  1 k  2  2k  9   k  N.
6
Consider, LHS = 1.3 + 2.4 + 3.5 + ... + (k + 1)(k + 3)
= 1.3 + 2.4 + 3.5 + ... + k(k + 2) + (k + 1)(k + 3)
6 Properties of Integers
--------------------------------------------------------------------------------------------------------------------------------------

k  k  1 2k  7 
= + (k + 1)(k + 3) (by using P(k))
6
k  k  1 2k  7   6  k  1 k  3
=
6
 k  1  k  2k  7   6  k  3 
=
6

 k  1  2k 2  13k  18
=
6

 k  1  2k 2  4k  9k  18
=
6
 k  1  2k  k  2   9  k  2  
=
6

=
 k  1 k  2  2k  9 
6
= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

6. Prove by mathematical induction for all positive integers n, that


1 1 1 1 n
   ...   .
1.4 4.7 7.10  3n  2  3n  1 3n  1
Solution:
1 1 1 1 n
Let P(n) =    ...    n  N.
1.4 4.7 7.10  3n  2  3n  1 3n  1
Step 1: For n =1,
1 1 1 1
LHS =  and RHS = 
1.4 4 3 1 4
So, LHS = RHS
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
1 1 1 1 k
Hence, P(k) =    ...    k  N.
1.4 4.7 7.10  3k  2  3k  1 3k  1
To show that P(k + 1) is true
1

1

1
 ... 
1

 k  1
i.e., P(k + 1) =
1.4 4.7 7.10  3  k  1  2   3  k  1  1 3  k  1  1
Discrete Mathematical Structures 7
-------------------------------------------------------------------------------------------------------------------------------------

1 1 1 1 k 1
 P(k + 1) =    ...    k  N.
1.4 4.7 7.10  3k  1 3k  4  3k  4
1 1 1 1
Consider, LHS =    ... 
1.4 4.7 7.10  3k  1 3k  4 
1 1 1 1 1
=    ...  
1.4 4.7 7.10  3k  2  3k  1  3k  1 3k  4 
k 1
=  (by using P(k))
3k  1  3k  1 3k  4 

k  3k  4   1
=
 3k  1 3k  4 
3k 2  4k  1
=
 3k  1 3k  4 
3k 2  3k  k  1
=
 3k  1 3k  4 
3k  k  1   k  1
=
 3k  1 3k  4 
 k  1 3k  1
=
 3k  1 3k  4 
k 1
=
3k  4
= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

7. Prove by Mathematical Induction (ab)n = anbn is true for every natural number n.
Solution:
Let P(n) = (ab)n = anbn for all n  N.
Step 1: For n =1,
LHS = (ab)1 = ab and RHS = a1b1 = ab
So, LHS = RHS
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = (ab)k = akbk  k  N.
8 Properties of Integers
--------------------------------------------------------------------------------------------------------------------------------------

To show that P(k + 1) is true


i.e., P(k + 1) = (ab)k + 1 = ak + 1bk + 1
Consider, (ab)k = akbk
Multiplying both side by 'ab'
(ab)k(ab) = (akbk)(ab)
 (ab)k + 1 = (aak )(bbk )
 (ab)k + 1 = ak + 1bk + 1
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

8. Establish each of the following by Mathematical Induction


n
1 n
(a)  i  i  1  n  1
i 1

n
(b) 2
i 1
i 1
 2n  1

 i  2   2   n  1 2
n
i n 1
(c)
i 1

n
(d)  i  i !   n  1!  1
i 1

Solution:
n
1 n
(a) Let P(n) =  i  i  1  n  1 for all n  N.
i 1

Step 1: For n =1,


1
1 1 n 1 1
LHS =  11  1  2 and RHS =
i1
 
n 1 11 2
So, LHS = RHS
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
k
1 k
Hence, P(k) =  i  i  1  k  1  k  N.
i 1

To show that P(k + 1) is true


k 1
1 k 1
i.e., P(k + 1) =  i  i  1   k  1  1
i 1
Discrete Mathematical Structures 9
-------------------------------------------------------------------------------------------------------------------------------------
k 1
1 k 1
 P(k + 1) =  i  i  1  k  2  k  N.
i 1

k 1
1
Consider, LHS =  i  i  1
i 1

k
1 1
=  i  i  1   k  1   k  1  1
i 1

k 1
=  (by using P(k))
k  1  k  1 k  2 

k  k  2  1
=
 k  1 k  2 
k 2  2k  1
=
 k  1 k  2 
 k  1
2

=
 k  1 k  2 
k 1
=
k 2
= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.
n
(b) Let P(n) = 2
i 1
i 1
 2n  1 for all n  N.

Step 1: For n =1,


1
LHS = 2
i 1
11
 20  1 and RHS = 21  1  2  1  1

So, LHS = RHS


 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
k
Hence, P(k) = 2
i 1
i 1
 2k  1

To show that P(k + 1) is true


k 1
i.e., P(k + 1) = 2 i 1
i 1
 2 k 1  1
10 Properties of Integers
--------------------------------------------------------------------------------------------------------------------------------------
k 1
Consider, LHS = 2 i 1
i 1

k
= 2 i 1
i 1
 2
k 1 1

= 2k  1  2k (by using P(k))


= 2  2k  1
= 2k 1  1
= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

 i  2   2   n  1 2
n
n 1
(c) Let P(n) = i
for all n  N.
i 1

Step 1: For n =1,

 i  2   1 2   2 and RHS = 2  1  1 2
1
11
LHS = i 1
 20  2
i 1

So, LHS = RHS


 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true

 i  2   2   k  1 2
k
i k 1
Hence, P(k) =
i 1

To show that P(k + 1) is true


k 1
i.e., P(k + 1) =  i  2   2    k  1  1 2
i 1
i k 1 1

k 1
 P(k + 1) =  i 2   2  k  2
i 1
i k 2

k 1
Consider, LHS = i 2 
i 1
i

 i  2    k  1  2 
k
i k 1
=
i 1

= 2   k  1 2 k 1   k  1  2 k 1  (by using P(k))

= 2  2 k 1  k  1   k  1 

= 2  2k 1  2k 
Discrete Mathematical Structures 11
-------------------------------------------------------------------------------------------------------------------------------------

= 2  k  2k  2 

= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.
n
(d) Let P(n) =  i  i !   n  1!  1 for all n  N.
i 1

Step 1: For n =1,


1
LHS =  i  i !  11!  1 and RHS = 1  1!  1  2  1  1
i 1

So, LHS = RHS


 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
k
Hence, P(k) =  i  i !   k  1!  1
i 1

To show that P(k + 1) is true


k 1
i.e., P(k + 1) =  i  i !    k  1  1!  1
i 1
k 1
 P(k + 1) =  i  i !   k  2 !  1
i 1
k 1
Consider, LHS =  i  i !
i 1

k
=  i  i !   k  1 k  1!
i 1

=  k  1!  1   k  1 k  1! (by using P(k))

=  k  1 ! 1   k  1   1

=  k  1!  k  2  1

=  k  2 !  1

= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.
12 Properties of Integers
--------------------------------------------------------------------------------------------------------------------------------------

9. Prove by Mathematical Induction n!  2n – 1 for all integers n  1.


Solution:
Let P(n) = n!  2n – 1 for all integers n  1.
Step 1: For n =1,
P(1) = 1!  21 – 1 = 1  1 which is true.
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = k!  2k – 1 or P(k) = 2k – 1  k!  k  1
To show that P(k + 1) is true
i.e., P(k + 1) = (k + 1)!  2(k + 1) – 1
 P(k + 1) = (k + 1)!  2k
Now, 2k = 2  2k – 1  2  k! (by using P(k))
 2k  (k + 1)  k! because 2  k + 1 for k  1
 2k  (k + 1)!
 (k + 1)!  2k
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  1.

10. Prove that for all n Z+, n > 3  2n < n!


Solution:
Let P(n) = 2n < n! for all integers n  4.
Step 1: For n = 4,
P(4) = 24 < 4! = 16 < 24 which is true.
 P(4) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = 2k < k!  k  4
To show that P(k + 1) is true
i.e., P(k + 1) = 2(k + 1) < (k + 1)!
Now, 2(k + 1) = 2  2k < 2  k! (by using P(k))
 2(k + 1) < (k + 1)  k! because 2 < k + 1 for k  4
 2(k + 1) < (k + 1)!
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  4.
Discrete Mathematical Structures 13
-------------------------------------------------------------------------------------------------------------------------------------

11. Prove by Mathematical Induction 4n < (n2 – 7) for all integers n  6.


Solution:
Let P(n) = 4n < (n2 – 7) for all integers n  6.
Step 1: For n = 6,
P(6) = 4(6) < (62 – 7) = 24 < 29 which is true.
 P(6) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = 4k < (k2 – 7)  k  6
To show that P(k + 1) is true
i.e., P(k + 1) = 4(k + 1) < ((k + 1)2 – 7)
Now, 4(k + 1) = 4k + 4
< (k2 – 7) + 4 (by using P(k))
< (k2 – 7) + (2k + 1) because when k  6, we have 2k + 1  13 > 4
= (k + 1)2 – 7
 4(k + 1) < ((k + 1)2 – 7) for k  6
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  6.

12. Prove that for all n Z+, n > 4  n2 < 2n


Solution:
Let P(n) = n2 < 2n for all integers n  5.
Step 1: For n = 5,
P(5) = 52 < 25 = 25 < 32 which is true.
 P(5) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = k2 < 2k or 2k > k2  k  5
To show that P(k + 1) is true
i.e., P(k + 1) = (k + 1)2 < 2(k + 1)
Now, 2(k + 1) = 2  2k > 2  k2 (by using P(k))
> k2 + k2
> k2 + (2k + 1) because when k  5, we have k2 > (2k + 1)
> (k + 1)2
 (k + 1)2 < 2(k + 1) for k  5
14 Properties of Integers
--------------------------------------------------------------------------------------------------------------------------------------

 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  5.

13. Prove by Mathematical Induction 3n −1 is a multiple of 2 for n = 1, 2, 3...


Solution:
Let P(n) = 3n −1 is a multiple of 2 for n = 1, 2, 3...
Step 1: For n = 1,
P(1) = 31−1 = 3−1 = 2 which is a multiple of 2.
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = 3k −1 is a multiple of 2 for k = 1, 2, 3...
To show that P(k + 1) is true
i.e., P(k + 1) = 3k + 1 −1 is a multiple of 2
Now, 3k + 1 −1 = 3×3k −1= (2×3k) + (3k −1)
The first part (2×3k) is certain to be a multiple of 2 and the second part (3 k −1) is also
true from our assumption P(k).
Hence, 3k + 1 −1 is a multiple of 2.
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

14. Prove by mathematical induction that, for every positive integer ≥ ,


3 divides − .
Solution:
Let P(n) = 3 divides − for ≥2
Step 1: For n = 2,
P(2) = 3 divides 33 – 3 = 27 – 3 = 3 divides 24 which is true.
 P(2) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = 3 divides − for ≥2
To show that P(k + 1) is true
i.e., P(k + 1) = 3 divides ( + 1) − ( + 1)
Now, P(k + 1) – P(k) = ( + 1) − ( + 1) − +
= +3 +3 +1− −1− +
= 3( + )
Discrete Mathematical Structures 15
-------------------------------------------------------------------------------------------------------------------------------------

 P(k + 1) = P(k) + 3( + ) which is divisible by 3.


 3 divides ( + 1) − ( + 1)
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  2.

15. Prove by mathematical induction that, for any positive integer n, the number
+ is divisible by 133.
Solution:
Let P(n) = 11 + 12 is divisible by 133 for n = 1, 2, 3...
Step 1: For n = 1,
P(1) = 11 + 12 = 1331 + 1728 = 3059 which is divisible by 133.
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = 11 + 12 is divisible by 133 for k = 1, 2, 3...
To show that P(k + 1) is true
i.e., P(k + 1) = 11( )
+ 12 ( )
is divisible by 133
 P(k + 1) = 11 + 12 is divisible by 133
Now, P(k + 1) – P(k) = 11 + 12 – 11 − 12
= 11 (11 − 1) + 12 (12 − 1)
= 10(11 + 12 ) + 12 (133)
= 10 P(k) +12 (133)
 P(k + 1) = 11 P(k) +12 (133) which is divisible by 133.
Hence, 11 + 12 is divisible by 133
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

16. Prove by mathematical induction that, for every positive integer ,


= + . + is a multiple of 8.
Solution:
Let P(n) = = 5 + 2.3 + 1 is a multiple of 8 for n = 1, 2, 3...
Step 1: For n = 1,
P(1) = = 5 + 2.3 +1 =5+2+1= 8 which is a multiple of 8.
 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
16 Properties of Integers
--------------------------------------------------------------------------------------------------------------------------------------

Hence, P(k) = = 5 + 2.3 + 1 is a multiple of 8 for k = 1, 2, 3...


To show that P(k + 1) is true
i.e., P(k + 1) = =5 + 2.3 + 1 is a multiple of 8
Now, − = 5( +1)
+ 2.3( +1)−1
+ 1 − 5 − 2.3 −1
−1

= 5 (5 − 1) + 2.3 (3 − 1)
= 4(5 + 3 )
= 4(Even)
= + 4(Even), which is a multiple of 8.
Hence, =5 + 2.3 + 1 is a multiple of 8
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.

17. Prove that every positive integer ≥ can be written as a sum of 5’s and/or 7’s.
Solution:
Let P(n) = can be written as a sum of 5’s and/or 7’s for n ≥ 24
Step 1: For n = 24,
P(24) = 24 = 5 + 5 + 7 + 7 which is true
 P(24) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
Hence, P(k) = can be written as a sum of 5’s and/or 7’s for k ≥ 24
To show that P(k + 1) is true
i.e., P(k + 1) = ( + 1) can be written as a sum of 5’s and/or 7’s for k ≥ 24
Now, + 1 = (7 + 7 + ⋯ r times) + (5 + 5 + ⋯ s times) + 1
= (7 + 7 + ⋯ (r − 2)times) + (5 + 5 + ⋯ s times) + 7 + 7 + 1
= (7 + 7 + ⋯ (r − 2)times) + (5 + 5 + ⋯ s times) + 15
= (7 + 7 + ⋯ (r − 2)times) + (5 + 5 + ⋯ (s + 3) times)
= sum of 5’s and 7’s.
Hence, ( + 1) can be written as a sum of 5’s and/or 7’s for k ≥ 24
 P(k + 1) is true
Hence by the principle of induction P(n) is true for ≥ 24.
Discrete Mathematical Structures 17
-------------------------------------------------------------------------------------------------------------------------------------

1 1 1 1 1 1
18. Let H1  1, H 2  1  , H 3  1   , ..., H n  1    ...  .
2 2 3 2 3 n
n
Prove that  H   n  1 H
i 1
i n  n, for all positive integers n  1.

Solution:
1
By given data, H k  H k 1 
k 1
n
Let P(n) =  H   n  1 H
i 1
i n  n for all n  N.

Step 1: For n =1,


1
LHS = H
i 1
i  H1  1 and RHS = 1  1 H1  1   2 1  1  1

So, LHS = RHS


 P(1) is true
Step 2: Let us assume that the result is true for n = k, i.e., P(k) is true
k
Hence, P(k) =  H   k  1 H
i 1
i k  k  k  N.

To show that P(k + 1) is true


k 1
i.e., P(k + 1) =  H    k  1  1 H 
i 1
i k 1
  k  1
k 1
 P(k + 1) =  H   k  2 H
i 1
i k 1
  k  1

k 1
Consider, LHS = H
i 1
i

k
= H
i 1
i  H k 1

=  k  1 H k  k  H k 1 (by using P(k))

 1 
=  k  1  H k 1    k  H k 1 (by given data)
 k 1 

=  k  1 H k 1  1  k  H k 1

=  k  2  H k 1   k  1

= RHS
 P(k + 1) is true
Hence by the principle of induction P(n) is true for all n  N.
18 Properties of Integers
--------------------------------------------------------------------------------------------------------------------------------------

EXERCISE – 2.1

1. Prove by mathematical induction that for all positive integers ≥ 1,


n  3n  1
1 + 4 + 7 + … + (3n – 2) =
2
2. Prove by mathematical induction that for all positive integers ≥ 1,
n  2n  1 2n  1
12 + 32 + 52 + ... + (2n 1)2 =
3
3. Prove by mathematical induction that for all positive integers ≥ 1,
13 + 33 + 53 + ... + (2n 1)3 = n 2  2n 2  1 .
4. If is any positive integer prove that
1
1.2 + 2.3 + 3.4 + ⋯ + ( + 1) = ( + 1)( + 2)
3
5. Prove by mathematical induction that for all positive integers ≥ 1,
1
1.3 + 2.4 + 3.5 + ⋯ + ( + 2) = ( + 1)(2 + 7)
6
6. Prove by mathematical induction that for all positive integers ≥ 1,
1 1 1 1 1
+ + + ⋯+ =
1.3 3.5 5.7 (2 − 1)(2 + 1) 2 + 1
7. Prove by mathematical induction that for all positive integers ≥ 1,
1 1 1
+ + ⋯+ =
2.5 5.8 (3 − 1)(3 + 2) 6 + 4
8. Prove by mathematical induction that for all positive integers , 5 divides − .
9. Prove by mathematical induction that for all positive integers , 6 +7 is
divisible by 43.
10. Prove by mathematical induction that < 2 for all positive integers ≥ 1,
11. Prove that every positive integer is greater than or equal to 14 may be written as a
sum of 3’s and/or 8’s.
12. Prove by mathematical induction that for all positive integers ,
n
a   a  d    a  2d   ...   a   n  1 d    2a   n  1 d  .
2
13. Prove by mathematical induction that for r  1,

n 1
a 1  r n 
a  ar  ar  ...  ar
2
 .
1 r

14. Prove by mathematical induction that x n  y n is divisible by x – y.

You might also like